Combatting Venereal Diseases as an Instrument of Politicised Medicine: Analysis on the Example of the Soviet Occupation Zone in Germany, the German Democratic Republic, and the Polish Peoples’ Republic - Marcin Orzechowski; Maximilian Schochow; Florian Steger (Acta Medico-Historica Rigensia)
The programme for combatting venereal diseases in the Soviet Occupation Zone of Germany (SOZ), the German Democratic Republic (GDR) and the Polish Peoples’ Republic (PPR) after the Second World War was adopted from the Soviet healthcare model. In order to maintain the spread of infections, both countries introduced specific legislation. The analysis of the regulations shows several similarities, such as establishment of easy access to anti-venereal health services, interruption of the chain of infection, and special treatment of individuals who constituted a danger of spreading the infection through compulsory hospitalisation. However, some differences are also visible. In the PPR, the decision about compulsory hospitalisation was left to individual evaluation of the attending physician. Closed venereology facilities or reformatories for treatment of venereal diseases, which existed in the GDR, were not established through legal regulations in the PPR. Since 1964, Polish law specifically targeted prostitutes and alcoholics as sources of spreading venereal diseases. These groups were not mentioned in the German legal acts. Analysis of praxis of compulsory commitment in the SOZ and GDR shows that mostly young women characterized as “drifters” were sent to closed venereology wards with breach of legal regulations. The number of prostitutes constituted only a very small fraction. In the PPR, the data from contemporary literature also indicates a considerable number of young women, the so-called “drifters”, committed to venereology ward.